WEAKLY (tau(q),m)-CONTINUOUS FUNCTIONS - ŞENGÜL, UĞUR (UNIV AL I CUZA, FAC MATH, 2014)
In this paper we introduce a new class of functions called weakly (tau(q), m)continuous functions. Some characterizations and several properties concerning weak (tau(q), m)-continuity are obtained.
Keywords: m-structure; (tau(q),m)-continuity; weak (tau(q),m)-continuity; strongly clpm-closed graph; m(X)-regular set; ultra Hausdorff space; ultraregular space; SUPER-CONTINUITY; STRONG FORMS